The Implementation and Design of an Automatic LED Emergency Light System for Power Outages - TAREQ, SAJJAD LIWAA (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Growing demand for electricity savings has led to the development of an automatic LED emergency light system. It is based on providing light when the power is cut off. Once fully charged, the battery ceases charging, and in the event of a power failure, the LEDs are automatically powered by the battery. The project focuses on two primary functions: it automatically activates during power outages to give illumination, eliminating the need to search for the switch, and the battery rapidly begins recharging as the main power is restored. The emergency light is crucial due to the inconsistent voltage distribution and frequent power outages in operational regions of communities and diverse enterprises. The system includes a power supply that converts 230V AC to 12V DC, a relay that uses a control pulse to alternate between connecting the battery to the LEDs and isolating it, and a rechargeable Li-ion battery that supplies power to the LEDs during blackouts. The parallel-connected LEDs light up during a power outage in the circuits. The circuit architecture shown here serves to mitigate the entire discharge of the battery, hence enhancing the battery’s longevity. Key components of the system include a step-down transformer, a bridge circuit to convert AC to DC, a Zener diode to maintain voltage stability, capacitors for energy storage, and various diodes to control current flow. The project highlights the advantages of LED emergency lights, such as efficiency, longevity, and minimal energy waste, though it acknowledges the higher initial cost and temperature sensitivity as disadvantages. The automatic LED emergency light is suitable for use in homes, offices, retail shops, and other commercial settings. The project demonstrates a cost-effective and compact solution that enhances daily life by providing reliable lighting during power failures.